Le avventure delle pizie nella civiltà dell' alfabeto - Angela Giallongo (Firenze University Press, 2009)
The essay is a storiographical reflection about female teaching between Nineteenth and Twentieth century. Two are the most importan focus: the case of female teaching in Italy today and gender paradigm inside pedagogical research.